2014
DOI: 10.3109/01612840.2014.895071
|View full text |Cite
|
Sign up to set email alerts
|

Memory Performance and Affect: Are there Gender Differences in Community-Residing Older Adults?

Abstract: After age 65, the incidence of episodic memory decline in males is greater than in females. We explored the influence of anxiety and depression on objective and subjective memory performance in a diverse sample of community-residing older adults. The study was a secondary analysis of data on three samples of adults from two states, Ohio and Texas: a community sample (n = 177); a retirement community sample (n = 97); and the SeniorWISE Study (n = 265). The sample of 529 adults was 74% female, the average age wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…Prior studies have found evidence that hippocampal volumes, adjusted for total brain volume, are larger in women than men as they age (Braden et al, 2016;Jack et al, 2015). There is also evidence that women may utilize both internal and external memory strategies to a greater extent than men, which has been put forth as an explanation for the observed sex differences in memory, at least in healthy older adults (Kramer, Delis, & Daniel, 1988;McDougall, Pituch, Stanton, & Chang, 2014;Sunderaraman, Blumen, DeMatteo, Apa, & Cosentino, 2013). Future studies within our clinical sample aim to examine differences in hippocampal volumes as well as learning and memory strategies, specifically semantic clustering, and their relationships to the observed sex differences in verbal learning and memory.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Prior studies have found evidence that hippocampal volumes, adjusted for total brain volume, are larger in women than men as they age (Braden et al, 2016;Jack et al, 2015). There is also evidence that women may utilize both internal and external memory strategies to a greater extent than men, which has been put forth as an explanation for the observed sex differences in memory, at least in healthy older adults (Kramer, Delis, & Daniel, 1988;McDougall, Pituch, Stanton, & Chang, 2014;Sunderaraman, Blumen, DeMatteo, Apa, & Cosentino, 2013). Future studies within our clinical sample aim to examine differences in hippocampal volumes as well as learning and memory strategies, specifically semantic clustering, and their relationships to the observed sex differences in verbal learning and memory.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Higher general cognitive ability was weakly associated with more IMS and EMS ( rs = .14–.30; McDougall et al, 2014; Raimo et al, 2016). In a nursing home sample, individuals with the lowest general cognitive ability reported more IMS than those who scored higher (McDougall, 1995b).…”
Section: Resultsmentioning
confidence: 99%
“…All six studies were cross-sectional, though one study (Hertzog, Small et al 2019) also reported longitudinal data. Women reported more frequent IMS in two studies (rs = À.14 to À.18; de Frias et al, 2003;Hertzog, Small et al 2019), while three others found no relationship (rs < .09; ds < .20; de Frias, 2014;McDougall et al, 2014;Ponds & Jolles, 1996). More consistently, women reported more frequent EMS (rs = À.12 to À.28; ds = .34 to .44; de Frias, 2014;de Frias et al, 2003;McDougall et al, 2014;Ponds & Jolles, 1996).…”
Section: Demographic Correlatesmentioning
confidence: 91%
See 2 more Smart Citations